Quantitative analysis of irrigation water productivity in the middle reaches of Heihe River Basin, Northwest China - Li, Donghao; Du, Taisheng; Cao, Yue; Shukla, Manoj Kumar; Wu, Di; Guo, Xiuwei; Chen, Shichao (International Journal of Agricultural and Biological Engineering, 2019)
With the growing shortage of surface water resources, it is of great significance for improving the irrigation water productivity (IWP) to ensure the water and food security. The contribution of the driving factors of the IWP and the rational regulation of the input factors of agricultural production is required. In this paper, 118 and 80 sampling points were selected in Pingchuan and Liaoquan irrigation districts (PLID, the spacing of sampling point is approximately 1 km) and the middle reaches of the Heihe River basin (MHRB, the spacing of sampling point is approximately 10 km), respectively. Soil characteristics and management measures near the sampling points were obtained. Results showed that the average value of the IWP in MHRB was 1.67 kg/m3, with a moderate heterogeneity in the space. The main driving factors of IWP were irrigation, fertilization and planting density. On the PLID, the contribution rates of soil factors and management measures to IWP were 20.6% and 35.2%, respectively, and the contribution of soil factors to IWP increased to 43.8% in the MHRB, while the contribution rate of management measures decreased to 24.8%. It shows that in a small irrigation districts, from the perspective of farmers, the improvement of IWP should be mainly controlled by management measures, while in the large area of watershed scale, the spatial differences in soil factors also need to be considered by the government management departments, when they want to increase IWP through regulating management measures. Keywords: irrigation water productivity, driving factors, quantitative analysis, partial least squares, maize DOI: 10.25165/j.ijabe.20191205.4759 Citation: Li D H, Du T S, Cao Y, Shukla M K, Wu D, Guo X W, et al. Quantitative analysis of irrigation water productivity in the middle reaches of Heihe River Basin, Northwest China. Int J Agric & Biol Eng, 2019; 12(5): 119–125.